Hemangioma of the Tympanic Membrane: A Case and a Review of the Literature. (2nd December 2012) - Mevio, Emilio; Cazzaniga, Marco; Mullace, Mauro; Paolotti, Donatella
Abstract : Hemangiomas of the external auditory canal, involving the posterior bony canal and the adjacent tympanic membrane, although rare, are considered a specific disease entity of the human external auditory canal. Hemangiomas of the tympanic membrane and/or external auditory canal are rare entities; there are 16 previous case reports in the literature. It is a benign vascular tumor. It generally occurs in males in the sixth decade of life. Total surgical excision with or without tympanic membrane grafting appears to be effective in the removal of this benign neoplasm. The authors present a case and a review of the literature discussing diagnostic and surgical approaches.